APPLICATION OF COGNITIVE BEHAVIORAL THERAPY (CBT) THEORY TO IMPROVE SELF-EFFICACY AND MOTIVATION IN MEMORIZING THE QUR'AN - Khomsatur Rohmah; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research is motivated by the problem of low self-efficacy (self-confidence) in some students who memorize the Qur'an, which has an impact on decreasing motivation and memorization targets. Negative thoughts such as feelings of inadequacy, fear of forgetting, and mental fatigue often hinder the memorization process, as well as cognitive barriers (such as negative thoughts